A MLC-based inversely optimized 3D spatially fractionated grid radiotherapy technique. Issue 3 (December 2015) - Jin, Jian-Yue; Zhao, Bo; Kaminski, Joseph M.; Wen, Ning; Huang, Yimei; Vender, John; Chetty, Indrin J.; Kong, Feng-Ming (Spring)
Abstract: This study presents a MLC-based, 3D grid-therapy technique with characteristics of both 3D-conformal-radiotherapy and grid-therapy. It generates a brachytherapy-like dose distribution, with D50% of 20, 9.8, 5.4 and 2.9-Gy, for the spheres, target, 1 cm-outershell and 2 cm-outershell, respectively. It may provide a strategy to deliver ablative doses to large tumors safely.